Educational management system of colleges and universities based on embedded system and artificial intelligence - Wang, Yashu (Microprocessors and microsystems, 2021)
We use education management service is to ensure the normal development of education management in Colleges and universities, to support and guarantee its role.In the establishment of the corresponding system, we are involved in all aspects of the problem, which is very complex.In theory, we include school education, network security and social environment and other aspects.Based on these factors and causality, we propose a simulation model which can dynamically analyze the role of students in education management services.Our simulation results are in good agreement with the actual results, and we propose an improved scheme based on the experimental results.With the development of science and technology, artificial intelligence technology is also in continuous progress, now all fields of talent at all levels are studying artificial intelligence technology, and have different views on it.From the current trend, we can see that in the future, artificial intelligence technology will certainly involve all aspects of people's life, and play an obvious role in improving people's quality of life.At the same time, artificial intelligence technology can also be applied in the education industry. The combination of human intelligence technology and education management technology makes the management of education more leisurely and active, and can promote the development of education management.However, with the integration of artificial intelligence technology and education management technology, there will be a series of negative problems and privacy leakage risks, which also brings some challenges and difficulties to the education management industry.